Retrospective analysis of the efficacy of percutaneous transhepatic biliary drainage in palliation of obstructive jaundice in patients with carcinoma gall bladder: Experience from tertiary care center in Northern India - Sawant, Milind B.; S. Harish; Nishant Lohia; S. Anand; Manoj Prashar; Sankalp Singh; Gaurav Trivedi (Asian Journal of Medical Sciences, 2021)
Background: Percutaneous Transhepatic Biliary Drainage (PTBD) is a minimally invasive procedure to palliate the biliary obstruction caused by unresectable malignancy. Aims and Objective: To analyze the outcome of PTBD in patients of unresectable gall bladder cancer presenting with obstructive jaundice in terms of reduction in serum bilirubin levels, symptomatic improvement, and overall survival (OS) at 4 weeks and 12 weeks following the procedure. Materials and Methods: In this retrospective study, PTBD was attempted on 30 patients diagnosed with inoperable gall bladder cancer. Various patient and procedure-related variables were analyzed and recorded both pre and post-PTBD. Outcome data on OS was collected at 4 weeks and 12 weeks. Results: Technical success was achieved in 29 (99.66%) patients. The mean fall in the serum bilirubin at the 7th post-procedural day was 41.5% after the successful PTBD. The most common complication in our study was cholangitis noted in six (21%) patients. OS at 4 weeks and 12 weeks was 79% and 41%, respectively. Conclusion: Younger age and good performance status favored better survival rate in our study.